How many numbers of sequence , , ..... are perfect squares ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Lets see, that the first number that work is 1. Now let find a greater one digit number. We can see the numbers are in the form k ( k k k . . . k k k ) with the second k ‘ s written k times. See k ( k k k . . . k k k ) = k 2 ( 1 1 1 . . . 1 1 1 ) with the 1 ‘ s written k times. So, if k 2 ( 1 1 1 . . . 1 1 1 ) is a square, then, ( 1 1 1 . . . 1 1 1 ) is a square.
See 1 1 1 . . . 1 1 1 = 1 + 1 0 + . . . + 1 0 k − 1 = 9 1 0 k − 1 ; so 9 1 0 k − 1 is a square if 1 0 k − 1 is also a square.
1 0 k − 1 = 9 9 9 . . . 9 9 9 with the 9 ‘ s written k times. After seeing the quadratic residues m o d 1 0 we know that the units digits is 3 or 7 . Now, we check the residues m o d 1 0 0 with the units digits 3 and 7 and it should be 99.
7 2 ≡ 4 9 , 1 7 2 ≡ 8 9 , 2 7 2 ≡ 2 9 , 3 7 2 ≡ 6 9 , 4 7 2 ≡ 9 , 5 7 2 ≡ 4 9 , 6 7 2 ≡ 8 9 , 7 7 2 ≡ 2 9 , 8 7 2 ≡ 6 9 , 9 7 2 ≡ 9 m o d 1 0 0 so 7 doesn`t works.
3 2 ≡ 9 , 1 3 2 ≡ 6 9 , 2 3 2 ≡ 2 9 , 3 3 2 ≡ 8 9 , 4 3 2 ≡ 4 9 , 5 3 2 ≡ 9 , 6 3 2 ≡ 6 9 , 7 3 2 ≡ 2 9 , 8 3 2 ≡ 8 9 , 9 3 2 ≡ 4 9 m o d 1 0 0 . So, 9 9 9 . . . 9 9 9 isn`t a square.
Now, let find a greater number , say N is a number with d digits. So, after some reasoning we can see that the first expression is N 2 ( 1 0 d − 1 + 1 0 2 ( d − 1 ) + . . . + 1 0 x ( d − 1 ) ) . So, as N 2 is a square, then ( 1 0 d − 1 + 1 0 2 ( d − 1 ) + . . . + 1 0 x ( d − 1 ) ) must be a square. Now, see 1 0 d − 1 + 1 0 2 ( d − 1 ) + . . . + 1 0 x ( d − 1 ) = 1 0 d − 1 ( 1 + 1 0 + . . . + 1 0 x ) , that is why it was important to see that 1 + 1 0 + . . . + 1 0 x isn`t a square.
Now, we have two cases:
1 ) If, d is odd, then clearly the expression isn`t a square.
2 ) If d is even then we can say that 1 0 d − 1 ( 1 + 1 0 + . . . + 1 0 x ) = 1 0 ∗ 1 0 2 m ( 1 + 1 0 + . . . + 1 0 x ) . So the expression is a square if and only if 1 0 ( 1 + 1 0 + . . . + 1 0 x ) but that is not possible because 1 0 and 1 + 1 0 + . . . + 1 0 x .
So, the only answer is 1 .